2009
DOI: 10.1007/s11269-009-9481-7
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment Using Multivariate Statistical Methods—A Case Study: Melen River System (Turkey)

Abstract: This study is focused on water quality of Melen River (Turkey) and evaluation of 26 physical and chemical pollution data obtained five monitoring stations during the period [1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006]. It presents the application of multivariate statistical methods to the data set, namely, principal component and factor analysis (PCA/FA), multiple regression analysis (MRA) and discriminant analysis (DA). The PCA/FA was employed to evaluate the high-low flow periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 24 publications
0
66
0
1
Order By: Relevance
“…To avoid duplicate tracks in dist (a, b), the Euclidean distance (euclidean), an application of the Malinowski space, was used. The Malinowski space can be solved using the matrix value of p = ∞ in Equation (4). The pdist shows that object ρ ∈ C Figure 1.…”
Section: Testbed Designmentioning
confidence: 99%
See 3 more Smart Citations
“…To avoid duplicate tracks in dist (a, b), the Euclidean distance (euclidean), an application of the Malinowski space, was used. The Malinowski space can be solved using the matrix value of p = ∞ in Equation (4). The pdist shows that object ρ ∈ C Figure 1.…”
Section: Testbed Designmentioning
confidence: 99%
“…Therefore, onitoring of urban streams is necessary to evaluate the impact of urban pollution on . Numerous methods exist to monitor and analyze these parameters, including discrete , water analysis, and use of monitoring networks [4]. However, continuous efficient www.mdpi.com/journal/wa…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of different mathematical tools, such as principal component analysis (PCA) and cluster analysis (CA), allows the interpretation of complex data matrices to better understand the water quality and ecological status of the studied system (Kotti et al 2005;Koklu et al 2010;Ogleni and Topal 2011;Awadallah and Yousry 2012). These studies showed the ability of PCA and CA for the evaluation and interpretation of complex data sets to get better information about water quality and the design of the monitoring network for effective management of water resources.…”
Section: Introductionmentioning
confidence: 99%